A microbially produced AhR ligand promotes a Tph1-driven tolerogenic program in multiple sclerosis - Zelante, Teresa; Paolicelli, Giuseppe; Fallarino, Francesca; Gargaro, Marco; Vascelli, Gianluca; De Zuani, Marco; Fric, Jan; Laznickova, Petra; Kohoutkova, Marcela Hortova; Macchiarulo, Antonio; Dolciami, Daniela; Pieraccini, Giuseppe; et al. (Scientific reports, 2024)
Multiple sclerosis is a debilitating autoimmune disease, characterized by chronic inflammation of the central nervous system. While the significance of the gut microbiome on multiple sclerosis pathogenesis is established, the underlining mechanisms are unknown. We found that serum levels of the microbial postbiotic tryptophan metabolite indole-3-carboxaldehyde (3-IAld) inversely correlated with disease duration in multiple sclerosis patients. Much like the host-derived tryptophan derivative L-Kynurenine, 3-IAld would bind and activate the Aryl hydrocarbon Receptor (AhR), which, in turn, controls endogenous tryptophan catabolic pathways. As a result, in peripheral lymph nodes, microbial 3-IAld, affected mast-cell tryptophan metabolism, forcing mast cells to produce serotonin via Tph1. We thus propose a protective role for AhR-mast-cell activation driven by the microbiome, whereby natural metabolites or postbiotics will have a physiological role in immune homeostasis and may act as therapeutic targets in autoimmune diseases.
Keywords: tryptofanhydroxylasa; Serotonin; Tryptophan Hydroxylase; Tryptophan; tryptofan; Humans; Aryl hydrocarbon receptor; kynurenin; Ligands; receptory aromatických uhlovodíků; roztroušená skleróza; Multiple sclerosis; Receptors, Aryl Hydrocarbon; Mast cells; Multiple Sclerosis; lidé; ligandy; Kynurenine; 3-IAld